The Development of Religious and Moral Values through Playing - Novienda, Ulfa Dina (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study aims to describe playing activities in the context of teaching religious and moral values in a kindergarten in Jember Regency, East Java Province, Indonesia. This type of research is descriptive and qualitative. The data collection techniques include interviews, observation, and documentation. Data analysis uses an interactive model through data reduction, presentation, and conclusion drawing. The method of checking the data's validity is through the source, technical, and time triangulation. This study's data sources were the board of teachers or educators and students aged 5 to 6 years in a kindergarten institution. This research focused on how educators develop religious and moral values ??through the play method using simple media, such as cards, balls, paper, and alphabet blocks. Penelitian ini bertujuan untuk mendeskripsikan aktivitas bermain dalam rangka penanaman nilai-nilai keagamaan dan nilai moral yang berlangsung di sebuah taman kanak-kanak di Kabupaten Jember, Provinsi Jawa Timur, Indonesia. Jenis penelitian ini adalah kualitatif deskriptif. Adapun teknik pengumpulan data meliputi wawancara, observasi dan dokumentasi. Analisis data menggunakan model interaktif melaluli reduksi data, penyajian data, penarikan kesimpulan. Teknik pemeriksaan keabsahan data melalui triangulasi sumber, triangulasi teknik, dan triangulasi waktu. Sumber data pada penelitian ini adalah dewan guru atau pendidik dan peserta didik berusia 5 sampai 6 tahun pada sebuah lembaga taman kanak-kanak. Penelitian ini difokuskan pada bagaimana cara pendidik mengembangkan nilai agama dan moral melalui metode bermain dengan memanfaatkan media sederhana, seperti kartu, bola, kertas, dan balok abjad.